ENHANCING THE PERFORMANCE OF SAVONIUS ROTOR USING TIERED-HEIGHT ZIGZAG PATTERNS IN CONCAVE SURFACE - Sumiati, Ruzita; Dinata, Uyung Gatot S.; Adi Saputra, Dendi (Journal of Applied Engineering Science, 2024)
A technique to reduce CO2 emissions from the use of fossil fuels is to use clean energy. One of them is wind energy, which is generated by a wind turbine. Savonius, a type of vertical axis wind turbine, is a small-scale energy conversion device suitable for low wind speeds, such as those characteristic of Indonesian wind speed. The objective of the current study was to analyze the impact of implementing a tiered-height zigzag pattern on the concave surface of the Savonius blade. The zigzag angle operates to direct the wind toward the reverse blade, consequently augmenting the pressure on the reverse blade. In addition, the tiered-height zigzag pattern in the concave surface increases the area of the turbine that is in contact with the wind, which in turn generates more energy. This study used an open-type wind tunnel to conduct experiments as the primary technique of investigation. Its performance was assessed in terms of power and torque coefficients. Additionally, experiments were conducted with other standard semi-circular blades to get a direct comparison. According to the findings of the experiments, incorporating a tiered-height zigzag pattern into a concave surface may produce a power coefficient (Cp) that is 16 % higher than that of a semi-circular. The highest Cp was 0.286 at a TSR of 0.55 and U = 6 m/s. In this case, the Savonius wind turbine’s ability may be elevated by including a tiered-height zigzag pattern in the Savonius concave surface.